Revealing the Short‐Circuiting Mechanism of Garnet‐Based Solid‐State Electrolyte. Issue 21 (8th April 2019) - Song, Yongli; Yang, Luyi; Zhao, Wenguang; Wang, Zijian; Zhao, Yan; Wang, Ziqi; Zhao, Qinghe; Liu, Hao; Pan, Feng
Abstract: Garnet‐type solid‐state electrolytes (SSEs) have been widely studied as a promising candidate for Li metal batteries. Despite the common belief that inorganic SSEs can prevent dendrite propagation, garnet SSEs suffer from relatively low critical current density (CCD) at which the SSEs are abruptly short‐circuited by Li dendrites. In this study, the short‐circuiting mechanism of garnet Li7 La2.75 Ca0.25 Zr1.75 Nb0.25 O12 (LLCZN) is investigated. It is found that instead of propagating uniaxially from one electrode to other in a dendritic form, metallic lithium is formed within the SSE. This can be attributed to the fact that electrons combine with Li ions at the grain boundary, which exhibits relatively high electronic conductivity, and then reduce Li + to Li 0 to cause short circuits. In order to reduce the electronic conductivity at the grain boundary, a thin layer of LiAlO2 is coated on the grain surface of LLCZN, which results in an improved CCD value. It is also found that under higher external voltages, the electronic conductivity of SSE becomes more significant, which is believed to be the origin of CCD. These findings not only shed light on the short‐circuiting mechanism of garnet‐type SSEs but also offer a novel perspective and useful guidance on their designs and modifications. Abstract : The short‐circuiting mechanism of garnet Li7 La2.75 Ca0.25 Zr1.75 Nb0.25 O12 (LLCZN) is investigated . Instead of propagating uniaxially from one electrode to the other in a dendritic form, metallic lithium is formed within the solid‐state electrolytes. It is found that the grain boundaries of LLCZN provide electron pathways, which allow Li + to be reduced.